Effects of foreign acquisitions on R&D and high-skill activities - Kent Eliasson; Pär Hansson; Markus Lindvert (Örebro University School of Business, 2015)
Using Swedish micro data we find no evidence for the concerns circulating in the public debate that foreign acquisitions lead to reductions in R&D expenditures and high-skilled activities in targeted domestic firms, neither in MNEs nor in non-MNEs. Previous studies have only focused on larger firms. In this paper we are able to study the impact on smaller firms (less than 50 employees). This is important since 90 percent of the firms acquired by foreign enterprises have less than 50 employees. For this group of firms there is no information on R&D, but by using the register of educational attainment we have data on the share of high-skilled labor in all Swedish firms, irrespective of size. Interestingly, we find that among smaller firms foreign enterprises tend to acquire high-productive, skill-intensive firms (cherry-picking) and after the acquisitions skill upgrading appears in acquired smaller, non- MNE firms.
Keywords: F23; J24; O32; O33; 330; foreign acquisitions; skill upgrading; R&D; intensity; propensity score matching